Deep proteomic profiling of human carotid atherosclerotic plaques using multidimensional LC-MS/MS - Sze, Siu Kwan (2014)
Purpose: To increase the proteome coverage of human atherosclerotic plaques and identify low-abundance proteins that may have important functions during the development and progression of atherosclerosis. Experimental design: Thirty-eight human carotid atherosclerotic plaques were pooled into two samples and analyzed in triplicate using offline multidimensional LC-MS/MS. The collected fractions of trypsin-digested peptides from Electrostatic Repulsion-Hydrophilic Interaction Chromatography (ERLIC) were analyzed by LC-MS/MS on a Q Exactive (Thermo Fisher, MA, USA). Results: A total of 4702 proteins were identified from atherosclerotic plaques at a false discovery rate (FDR) of 1%, of which 3846 were identified with at least 2 unique peptides. Many pathways related to the development and progression of atherosclerosis were identified, such as atherosclerosis signaling, toll receptor signaling pathway and inhibition of matrix metalloproteases. Many low-abundance proteins with important functions in atherosclerosis that were previously unidentifiable using mass spectrometry based proteomics methods, such as TGF-β, interleukins and other growth factors, were identified confidently from plaques. Conclusions and clinical relevance: This study has substantially increased the coverage of the atherosclerotic plaque proteome which represents a leap forward in understanding of plaque composition, development and progression. The identification of many low-abundance proteins may also facilitate biomarker discovery.